A systematic review of clinical outcomes for outpatient vs. inpatient shoulder arthroplasty. (October 2022) - Perera, Edward; Flood, Breanne; Madden, Kim; Goel, Danny P; Leroux, Timothy; Khan, Moin
Background: Outpatient shoulder arthroplasty is growing in popularity as a cost-effective and potentially equally safe alternative to inpatient arthroplasty. The aim of this study was to investigate literature relating to outpatient shoulder arthroplasty, looking at clinical outcomes, complications, readmission, and cost compared to inpatient arthroplasty. Methods: We conducted a systematic review of Medline, Embase and Cochrane Library databases from inception to 6 April 2020. Methodological quality was assessed using MINORS and GRADE criteria. Results: We included 17 studies, with 11 included in meta-analyses and 6 in narrative review. A meta-analysis of hospital readmissions demonstrated no statistically significant difference between outpatient and inpatient cohorts (OR = 0.89, p  = 0.49). Pooled post-operative complications identified decreased complications in those undergoing outpatient surgery (OR = 0.70, p  = 0.02). Considerable cost saving of between $3614 and $53, 202 (19.7–69.9%) per patient were present in the outpatient setting. Overall study quality was low and presented a serious risk of bias. Discussion: Shoulder arthroplasty in the outpatient setting appears to be as safe as shoulder arthroplasty in the inpatient setting, with a significant reduction in cost. However, this is based on low quality evidence and high risk of bias suggests further research is needed to substantiate these findings.